The MRN complex promotes DNA repair by homologous recombination and restrains antigenic variation in African trypanosomes - Mehnert, Ann-Kathrin; Prorocic, Marco; Dujeancourt-Henry, Annick; Hutchinson, Sebastian; McCulloch, Richard; Glover, Lucy (Nucleic acids research, 2021)
Homologous recombination dominates as the major form of DNA repair in Trypanosoma brucei, and is especially important for recombination of the subtelomeric variant surface glycoprotein during antigenic variation. RAD50, a component of the MRN complex (MRE11, RAD50, NBS1), is central to homologous recombination through facilitating resection and governing the DNA damage response. The function of RAD50 in trypanosomes is untested. Here we report that RAD50 and MRE11 are required for RAD51-dependent homologous recombination and phosphorylation of histone H2A following a DNA double strand break (DSB), but neither MRE11 nor RAD50 substantially influence DSB resection at a chromosome-internal locus. In addition, we reveal intrinsic separation-of-function between T. brucei RAD50 and MRE11, with only RAD50 suppressing DSB repair using donors with short stretches of homology at a subtelomeric locus, and only MRE11 directing DSB resection at the same locus. Finally, we show that loss of either MRE11 or RAD50 causes a greater diversity of expressed VSG variants following DSB repair. We conclude that MRN promotes stringent homologous recombination at subtelomeric loci and restrains antigenic variation.